On the behavior of solutions of operator-differential equations at infinity - Butyrin, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
The existence of limits at the infinity, generalized in the Abel sense, is established for bounded solutionsof the operator-differential equation $y'(t) = Ay(t)$ in a reflexive Banach space.